Physicochemical Pretreatment of Landfill Leachate - Chaudhuri, M.; Elmolla, E. S.; Heng, G. C. (2009)
The objective of the research was to study physicochemical pretreatment to prepare a landfill leachate for further treatment. Leachate samples were subjected to pH adjustment-settling and coagulation-flocculation. The pH adjustment-settling produced the following removals at pH 3: COD 45%, total suspended solids 80% and turbidity 59%. Coagulation-flocculation at optimum pH 6 and optimum FeCl3 dosage of 1200 mg/L resulted in COD, total suspended solids and turbidity removal of 65, 72 and 92%, respectively, and biodegradability was 0.18. pH adjustment-settling appears to be an adequate pretreatment for further treatment of the leachate by physicochemical process(es) operating at low pH such as Fenton treatment. Coagulation-flocculation appears to be a suitable pretreatment for further treatment of the leachate by biological process(es).